Microorganisms isolated from polluted urban soils highly effectives in degrading recalcitrant pesticides (2016)
Between 1972 and 1984 all types of solid waste from the city of Medellin were deposited in an area which had no technical specification as a landfill. Domestic, hospital and industrial waste was deposited, and accumulated to form a mountain of waste more than 10 meters high. To exacerbate the problem, when the site was closed for the deposit of solid waste, people remained living there to recycle materials. A study funded by the Valle de Aburrá Metropolitan Area and carried out by the GDCON Group at the Universidad de Antioquia between 2004 and 2005 found that leachate from the rubbish dump of Moravia contained heavy metals, phenols, sulphides, benzene, toluene, xylene, etc. In another study carried out by the GDCON and National University of Colombia (Medellín) between 2007 and 2009, it was found that plants and animals (mice, cockroaches etc.) in Moravia also contained these toxic pollutants. For this reason, the government of Medellin decided to move the people living in Moravia to another site in Medellin (between 2010 and 2014). Microbial consortia isolated from Moravia soils (MS) showed a high capacity to degrade chlorpyrifos, methyl parathion and malathion pesticides (20, 30 and 130 mg Kg-1). To provide a point of comparison, the degradation of the 3 pesticides was also performed with isolated pools of immature compost. The MS microbial consortia showed higher degradation rates than CI microbial consortia when malathion, methyl parathion and chlorpyrifos were degraded.